Spreading your bets, podcasting provides another platform for large organizations to reach a diverse audience - Cassidy, Stephen (Technical Centre for Agricultural and Rural Cooperation, 2007)
It is diffi cult for large organizations to target a specifi c audience when they produce information on a wide range of subjects. One solution is to make it easier for people to fi nd their stories